The effect of online collaborative writing instruction on enhancing writing performance, writing motivation, and writing self-efficacy of Chinese EFL learners - Li, Yan (Frontiers in Psychology, 2023)
This study aimed to examine the impact of online collaborative writing instruction on Chinese English as a foreign language (EFL) learners' writing performance, writing self-efficacy, and writing motivation. The study took place in a language school in mainland China and included 58 participants, with 30 in the experimental group and 28 in the control group. The experimental group received regular in-class writing instruction and used Tencent WPS Office, while the control group only received in-class instruction. The study lasted for 13 weeks and the writing tasks and writing motivation as well as writing self-efficacy scales were used for data collection. The results showed that the experimental group had greater significant improvement in writing performance, motivation, and self-efficacy than the control group, indicating the positive effect of using Tencent WPS Office for collaborative writing instruction. This study provides valuable information for language educators on the advantages of using online tools in improving EFL learners' writing skills.